1992
DOI: 10.3171/jns.1992.77.1.0127
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion of the pig superior sagittal sinus, bridging and cortical veins: multistep evolution of sinus-vein thrombosis

Abstract: Cerebral sinus-vein thrombosis may lead to severe hemodynamic changes, elevated intracranial pressure (ICP), and brain edema. It is supposed that progression of the thrombus from the sinus into bridging and cortical veins plays a key role in the development of these pathophysiological changes, but this hypothesis lacks experimental proof. The aim of this study, using a novel animal model of sinus-vein thrombosis, was to evaluate the effects of a standardized occlusion of the superior sagittal sinus and its bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 18 publications
(2 reference statements)
2
53
0
Order By: Relevance
“…Experimental data suggest that severe increases of rcp occur in response to thrombosis of cortical bridging veins (Fries et al, 1992;Frerichs et al, 1994). The con tribution of increased ICP to the reduction of CBF, how ever, is still controversial, and the elevation of the ve nous pressure and the decreased cerebral perfusion pres sure have been proposed as more important factors (Wagner and Traystman, 1983;Gotoh et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data suggest that severe increases of rcp occur in response to thrombosis of cortical bridging veins (Fries et al, 1992;Frerichs et al, 1994). The con tribution of increased ICP to the reduction of CBF, how ever, is still controversial, and the elevation of the ve nous pressure and the decreased cerebral perfusion pres sure have been proposed as more important factors (Wagner and Traystman, 1983;Gotoh et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The severity of parenchymal injuries in experimental CSVT models has been considered proportional to the degree of venous occlusion. 5 The lack of correlation between the extent and site of thrombosis in the dural sinuses and location of brain lesions has been suggested in adults. 6 In this study, our aims were to evaluate the frequency and topographic distribution of brain lesions associated with CSVT in children and to try and compare the topographic distribution of brain lesions with known normal venous drainage and anatomy.…”
mentioning
confidence: 99%
“…4,40 Infarctions occur in ~ 50% of cases. 24 It is in these patients in whom more immediate and aggressive treatment is indicated.…”
Section: Clinical Course and Prognosismentioning
confidence: 99%
“…Clinicians must watch postoperatively for a decrease in the hematocrit level and clinical signs of hypovolemia, and they must transfuse as needed. 24 Additionally, Curtin, et al 15 demonstrated the usefulness of a combination of approaches in treating CVT. Balloon angioplasty, direct rtPA, and Angiojet thrombectomy were used due to lack of clinical improvement after 1 modality.…”
mentioning
confidence: 99%
See 1 more Smart Citation